Dual CuCl doped argyrodite superconductor to boost the interfacial compatibility and air stability for all solid-state lithium metal batteries. (December 2021) - Taklu, Bereket Woldegbreal; Su, Wei-Nien; Nikodimos, Yosef; Lakshmanan, Keseven; Temesgen, Nigusu Tiruneh; Lin, Pei-Xuan; Jiang, Shi-Kai; Huang, Chen-Jui; Wang, Di-Yan; Sheu, Hwo-Shuenn; Wu, She-Huang; Hwang, Bing Joe
Abstract: The decent ductileness, high ionic conductivity, low cost, and versatility over synthesis methods make Li-argyrodite a promising for all-solid-state lithium batteries. However, its serious interfacial incompatibility with Li anode, dendrite growth, and intrinsic air instability impedes its practicability. Herein, we report a CuCl dual doped Li-argyrodite sulfide superb-conductor (Li6+3x P1−x Cux S5−x Cl1+x ) prepared to overcome these issues via ball-mill free synthesis approach . The maximum Li + conductivity of 4.34 mS cm −1 at room temperature with ultrawide voltage stability up to 8 V vs. Li/Li + was achieved in Li6.3 P0.9 Cu0.1 S4.9 Cl1.1 (LPSC-1) via a both composite and planar electrode system and can suppress dendrite formation at a current density of 3 mA cm −2 at 50  о C. The symmetrical cell cycled at 0.1 and 1 mA cm −2 also demonstrates remarkable reversibility with negligible overpotential alteration for more than 2400 h and 400 h. An ex-situ XPS and AC impedance analysis proved enhanced interfacial compatibility at Li | SE and achieved a critical current density of 3 mA cm −2 . More interestingly, incorporating soft acid Cu in LPSC-1 boosts the air stability and suppresses H2 S generation by two-folds. The XRD for the LPSC-1 before and after air exposure proves the decrease in the oxophilicity of the sulfide solid electrolyte. Graphical Abstract: ga1 Highlights: Doping soft acid Cu in LPSC boosts the air stability and suppresses H2 S generation. Ultra-high Li metal capability at 0.1 mA cm −2, 1 mA cm −2 and 3 mA cm −2 . Ionic conductivity of 4.34 mS cm −1 at RT with extended voltage stability, 8 V. Superior dendrite suppression capability with CCD 3 mA cm −2 at 50  о C. Decrease in oxophilicity with structural stability confirmed via XRD.